2022
DOI: 10.3389/fped.2022.996213
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and outcome predictors of a Chinese childhood-onset myasthenia gravis cohort

Abstract: Myasthenia gravis is an organ-specific autoimmune disease. Currently there is no universal guidelines for childhood-onset myasthenia gravis, therefore, treatment strategies are usually based on the guidelines from adult myasthenia gravis patients. In order to contribute in the process of the development of the universal childhood-onset myasthenia gravis guideline, we have summarized the clinical characteristics, treatment strategies, outcome and the related predictors of childhood-onset myasthenia gravis. We r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…However, OMG may progress to GMG [19]. In their large cohort study, Yang et al reported that 19 of 161 cases of juvenile OMG progressed to GMG with a median duration of 68 months [5]. They also noted that over 50% of the patients progressed to GMG in less than 2 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, OMG may progress to GMG [19]. In their large cohort study, Yang et al reported that 19 of 161 cases of juvenile OMG progressed to GMG with a median duration of 68 months [5]. They also noted that over 50% of the patients progressed to GMG in less than 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, all patients showed only ocular symptoms and were diagnosed with OMG; eventually, five cases (26.3%) progressed to GMG. The analysis of the factors which related to progression to GMG, including gender, age of onset, AChR-Abs status, revealed no correlation between them [5]. Therefore, the cause of its progression is still not well understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, I will define childhood as 18 years of age or younger, including post-pubertal age. Another characteristic of childhood-onset MG is the ratio of ocular muscle type to generalized MG. As shown in Table 1, ocular MG accounts for a higher proportion of childhood MG in East Asia than in the West [14][15][16][17][18][19]21,[23][24][25] (Table 1). Vecchio et al, in a study in the UK, where other ethnic groups congregate, found that the ocular muscle type in childhood-onset MG with onset before age 16 was 92% for Afro-Caribbeans, 29% for Arabians, 62.5% for Asians, and 42.3% for Caucasians, with significant racial differences among races other than Caucasians and East Asians [24].…”
Section: Characteristics Of Childhood Onset; Frequency and Peak Age O...mentioning
confidence: 99%
“…This racial difference in epidemiologic frequency may be due to immunogenetic differences, and several HLA differences have been reported for autoimmune MG; Vandiedonck et al reported a strong correlation between MG with thymic hyperplasia and the 8.1 HLA haplotype [26]. HLA-A1-B8-DR3 is assigned to the 8.1 ancestral haplotype; Popperud et al examined this in Norwegians [27] and found a strong correlation between this ancestral haplotype 8.1 (AH8.1; A*01-B*08-C*07-DRB1*03:01-DQB1*02:01), as well as alleles correlated strongly with juvenile MG. At the same time, he reported that the Another characteristic of childhood-onset MG is the ratio of ocular muscle type to generalized MG. As shown in Table 1, ocular MG accounts for a higher proportion of childhood MG in East Asia than in the West [14][15][16][17][18][19]21,[23][24][25] (Table 1). Vecchio et al, in a study in the UK, where other ethnic groups congregate, found that the ocular muscle type in childhood-onset MG with onset before age 16 was 92% for Afro-Caribbeans, 29% for Arabians, 62.5% for Asians, and 42.3% for Caucasians, with significant racial differences among races other than Caucasians and East Asians [24].…”
Section: Immunogenetic Studiesmentioning
confidence: 99%